ITO-free highly bendable and efficient organic solar cells with Ag nanomesh/ZnO hybrid electrodes. Issue 1 (3rd November 2014) - Song, Myungkwan; Kim, Han-Jung; Kim, Chang Su; Jeong, Jun-Ho; Cho, Changsoon; Lee, Jung-Yong; Jin, Sung-Ho; Choi, Dae-Geun; Kim, Dong-Ho
Abstract : High efficiency and bendable organic solar cells were fabricated using Ag nanomesh/ZnO hybrid transparent electrodes. Abstract : We demonstrate a facile approach to fabricate Ag nanomesh transparent conducting electrodes (TCEs) on a flexible substrate using nanoimprint lithography (NIL) and transfer printing without a conducting polymer. The Ag nanomesh TCEs exhibited a high transmittance of ∼88% and a low sheet resistance of ∼15 Ω sq −1 as well as superior mechanical flexibility. Furthermore, flexible inverted organic solar cells (IOSCs) with Ag nanomesh TCEs exhibited a power conversion efficiency (PCE) of ∼7.15% under 100 mW cm −2 AM 1.5G illumination as well as superior long-term stability under ambient conditions. This type of highly flexible and transparent Ag nanomesh electrode is a promising candidate for use with TCEs in various optoelectronic devices.